Managing older people in primary care a practical guide - Gosney, Margot; Harris, Tess. (Oxford : Oxford University Press, 2009)
Packed full of practical and down to earth advice for clinicians specialising in the care of older people, this book examines real problems that present on a day-to-day basis in the primary care environment.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Older people -- Medical care; Primary care (Medicine)